2015
DOI: 10.1007/s00170-015-6792-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ductility for squeeze cast 2017 A wrought aluminum alloy using the Taguchi method

Abstract: In this paper, the influence of process parameters on the ductility during squeeze casting of 2017 A wrought aluminum alloy is studied. The Taguchi method of design of experiments was employed to optimize the process parameters and to increase the elongation percent. A 3-factor, 3-level casting experiment is conducted by Taguchi L 9 orthogonal array through the statistical design method. Then, the input parameters are considered here including squeeze pressure, melt temperature, and die preheating temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The optimum squeeze casting parameter 2017A wrought Al alloys were revealed: squeeze pressure equal to 90 MPa, melt temperature equal to 700 °C, and die preheating temperature equal to 200 °C [29] . The semisolid slurry of wrought 5052Al alloy and AlCu5MnTi alloy were prepared by the indirect ultrasonic vibration, and then shaped by direct squeeze casting [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum squeeze casting parameter 2017A wrought Al alloys were revealed: squeeze pressure equal to 90 MPa, melt temperature equal to 700 °C, and die preheating temperature equal to 200 °C [29] . The semisolid slurry of wrought 5052Al alloy and AlCu5MnTi alloy were prepared by the indirect ultrasonic vibration, and then shaped by direct squeeze casting [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the percentage contribution (P) indicates the significance of process factors for the response. For a factor with a high values of P, a small variation will have a great influence on the performance (10). The graphical representation of percentage contribution is presented in Figure 4, it observed that, current (A) was found to be a major factor affecting the welding process significantly the mean average of UTS of 38.64%.…”
Section: Figure 3 Ga Convergence Plotmentioning
confidence: 93%
“…The Statistical Taguchi method is applied to model and optimize the squeeze casting parameters (that is, applied pressure, die and pouring temperature) for higher hardness, and UTS [10], and density, and SR [11] and ductility [12]. Taguchi method applied to optimize the parameters (die materialstainless steel, brass, SG iron, and copper, die temperature, pouring temperature, squeeze pressure) for enhanced wear resistance of AC2A alloy [13].…”
Section: Introductionmentioning
confidence: 99%